Pengembangan Jiwa Entrepreneur Syariah Melalui Pelatihan Manajemen Bisnis bagi Santri Pondok Pesantren Mawaridussalam - M. Guffar Harahap; Aswin Fahmin Darma; M. Radiansyah (CV. BAROKAH PUBLISHER, 2026)
This study aims to analyze the development of Islamic entrepreneurial spirit through business management training for students of Mawaridussalam Islamic Boarding School. The development of sharia-based entrepreneurship is important because it can foster students’ economic independence while instilling Islamic values in business activities. This study employed a library research method with a descriptive qualitative approach. The data were collected from various scientific sources, including national and international journal articles, books, and other scholarly publications related to Islamic entrepreneurship, santripreneurship, Islamic boarding school education, and business management. The findings indicate that business management training plays a significant role in improving students’ understanding of Islamic entrepreneurship concepts, Islamic business ethics, business planning, financial management, marketing strategies, and sustainable business development. Furthermore, the training contributes to the formation of entrepreneurial characteristics such as discipline, responsibility, creativity, leadership, and teamwork skills. The implementation of structured and practice-oriented business management training encourages the emergence of independent, productive, and competitive santripreneurs. Therefore, the development of an Islamic entrepreneurial spirit through business management training can serve as an effective strategy for enhancing the quality of human resources in Islamic boarding schools and supporting sharia-based economic empowerment.